Site‐Selective Functionalization of Carboranes at the Electron‐Rich Boron Vertex: Photocatalytic B−C Coupling via a Carboranyl Cage Radical - Chen, Meng; Xu, Jingkai; Zhao, Deshi; Sun, Fangxiang; Tian, Songlin; Tu, Deshuang; Lu, Changsheng; Yan, Hong (Angewandte Chemie International Edition, 2022)
Functionalization of carboranes in a vertex‐specific manner is a perennial challenge. Here, we report a photocatalytic B−C coupling for the selective functionalization of carboranes at the boron site which is most distal to carbon. This reaction was achieved by the photo‐induced decarboxylation of carborane carboxylic acids to generate boron vertex‐centered carboranyl radicals. Theoretical calculations also demonstrate that the reaction more easily occurs at the boron site bearing higher electron density owing to the lower energy barrier for a single‐electron transfer to generate a carboranyl radical. By using this strategy, a number of functionalized carboranes could be accessed through alkylation, alkenylation, and heteroarylation under mild conditions. Moreover, both a highly efficient blue emitter with a solid‐state luminous efficiency of 42 % and a drug candidate for boron neutron capture therapy (BNCT) containing targeting and fluorine units were obtained. A new photocatalytic strategy for the site‐selective functionalization of carboranes was demonstrated by the photo‐induced decarboxylation of carborane carboxylic acids to generate boron‐vertex‐centered carboranyl radicals. This strategy enables facile construction of highly efficient blue emitters and drug candidates for boron neutron capture therapy (BNCT).